Trajectories of resting frontal brain activity and psychopathology in female adolescents exposed to child maltreatment. Issue 1 (12th November 2017) - Tang, Alva; Miskovic, Vladimir; Lahat, Ayelet; Tanaka, Masako; MacMillan, Harriet; Van Lieshout, Ryan J.; Schmidt, Louis A.
Abstract: Resting frontal electroencephalogram (EEG) alpha asymmetry patterns reflecting different affective and motivational tendencies have been proposed as a putative mechanism underlying resilience among maltreated youth. This 2‐year prospective study examined whether developmental stability of resting frontal alpha asymmetry moderated the relation between child maltreatment severity and psychopathology in female adolescents ( n  = 43; ages 12–16) recruited from child protection agencies. Results identified two trajectories of resting frontal asymmetry: 60.5% displayed stable right and 39.5% displayed stable left frontal alpha asymmetry. Although individuals with these alpha asymmetry profiles experienced comparable childhood trauma severity, adolescents with stable left alpha asymmetry and lower levels of trauma were less likely to present symptoms or an episode of posttraumatic stress disorder (PTSD) and depression over 2 years than those with stable right alpha asymmetry and lower levels of trauma. These findings suggest that developmental patterns of resting left frontal brain activity may buffer against psychopathology in maltreated female youth.